2018
DOI: 10.1016/j.schres.2018.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between the anticipation and experience of pleasure in people with schizophrenia: An experience sampling study

Abstract: In contrast with controls people with schizophrenia did not show a link between their predictions and the activities they engaged in. This appears to be an important process influencing functioning in people with psychosis. Future interventions targeting reduced functioning should focus on reinforcing the link between pleasure anticipation and goal-directed behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
(52 reference statements)
3
25
0
Order By: Relevance
“…Consistent with our findings, previous research showed that patients with MDD are less responsive to positive stimuli in a laboratory task (Bylsma et al, 2008). Research with patients suffering from schizophrenia has also demonstrated a dissociation between PA and consummatory pleasure, with intact PA function but altered hedonic experience in patients compared to healthy controls (Edwards et al, 2018). In a study designed to distinguish PA and consummatory pleasure, Heininga et al (2017) found that individuals with anhedonia reported a lower level of both PA and consummatory pleasure compared to individuals without anhedonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, previous research showed that patients with MDD are less responsive to positive stimuli in a laboratory task (Bylsma et al, 2008). Research with patients suffering from schizophrenia has also demonstrated a dissociation between PA and consummatory pleasure, with intact PA function but altered hedonic experience in patients compared to healthy controls (Edwards et al, 2018). In a study designed to distinguish PA and consummatory pleasure, Heininga et al (2017) found that individuals with anhedonia reported a lower level of both PA and consummatory pleasure compared to individuals without anhedonia.…”
Section: Discussionmentioning
confidence: 99%
“…By including questions regarding current and future activities, the design helps to ensure that ratings for consummatory pleasure and anticipatory pleasure were based on daily events rather than memory representations. The use of brief measures is common in ESM research because excessive length can compromise response quality and reduce compliance (Bakker et al, 2017; Starr and Hershenberg, 2017; Edwards et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using EMA, participants can report on qualities of social experiences during (or immediately following) a given social interaction. The majority of EMA studies have found that people with SZ spend approximately the same amount of time with others compared to healthy controls [1215]. People with and without SZ also do not appear to differ in the extent of involvement they report in a given social interaction [13,16], but see [17].…”
Section: Introductionmentioning
confidence: 99%
“…We used multi‐level logistic modelling with participant, our cluster variable, considered as a random‐effect, whereas the effects of the predictors (ie, SDNN and EDA) on the outcome variable (ie, symptoms distress present or absent) were described as fixed effects. Analysis was conducted using the XTMELOGIT command in Stata (Version 15) (StataCorp, ) in line with similar studies (eg, Edwards, Cella, Emsley, Tarrier, & Wykes, ; Kimhy, Myin‐Germeys, Palmier‐Claus, & Swendsen, ). The effect of predictors on the outcome, representing the regression coefficients, is expressed as Z scores and odd ratios.…”
Section: Methodsmentioning
confidence: 99%